USING EF KIDS & TEENS INDONESIA YOUTUBE CHANNEL IN TEACHING NARRATIVE TEXT TO THE FIRST-GRADE STUDENTS OF SMAN 10 MAKASSAR - Lestari, Nanik; Said, Abdul Muis (Univeristas Islam Negeri (UIN) Alauddin Makassar, 2023)
This study aims to find out the implementation of bilingual-based instruction in teaching English. This study was conducted at the eighth grade of SMPN 1 Sungguminasa. The method used in this research was qualitative with a case study approach. The instruments of this research were observation sheets, interview guidelines, recorder, and documentation. The result showed that bilingual-based instruction implemented by the teacher at SMPN 1 Sungguminasa was English-Indonesian instruction. The teacher used English and Indonesian in context greeting, introducing material, giving an explanation, giving direction/instruction, giving clarification, asking and answering the question, and in context closing activity. The teacher used two languages with translation strategy and alternated his languages from L1 (first language) to L2 (second language) or vice versa to make the learning process run effectively. The factors that cause the teacher to use bilingual-based instruction in learning English are: the teacher said that bilingual-based instruction is important to make the learning process run effectively, the way the students understand the learning material is different, and using bilingual-based instruction helps students easy to understand what is explained by the teacher. From the findings above, the researcher hopes that this research can be useful for further learning, especially for students of English Education Department at Alauddin State Islamic University of Makassar who will become teacher. Then this research will be presented to motivate them to improve their English teaching skills.